Factors Affecting Fraud Prevention : Organizational Culture, Human Resource Competence and the Role of The Internal Auditor - Didiet Adi Nugroho; Rizkita Sari; Cris Kuntadi (Dinasti International Journal of Education Management And Social Science, 2023)
Fraud is a potential hazard to an organization, one of which can lead to budget leaks. These problems can be suspected due to the influence of Organizational Culture, Competence of Human Resources and the Role of Internal Auditors. This article reviews the factors that affecting fraud prevention: organizational culture, human resource competence and the role of internal auditors, a literature study on State Financial Management. The purpose of this article is to build a hypothesis on the relationship between variables to be used in further research. The result of this literature review are : 1) organizational culture affects fraud prevention; 2) human resource competence affects fraud prevention; 3) the role of internal auditor affects fraud prevention.